The true history of the Hueter-Volkmann law - Bartoníček, Jan; Naňka, Ondřej (International orthopaedics, 2024)
INTRODUCTION: The Hueter-Volkmann law (HVL) of the response of growth plate to compression load is a basic concept in orthopaedics. However, little is known about the origin of HVL and its history. MATERIALS AND METHODS: A literature search was performed in original publications and historical sources. RESULTS: An analysis of all Volkmann´s and Hueter´s texts has shown that none of their publications was based on experiments, but on the data in the literature and their own clinical observations. They did not deal at all with the effect of pressure on the growth plate and mentioned this structure only marginally. The authors coined the opinion that increased pressure retards and decreased pressure accelerates bone growth. Julius Wolff criticized the HVL and concentrated all his arguments in the book "The law of bone remodeling". According to him, increased pressure leads to bone formation, decreased pressure to its resorption. The Wolff-Volkmann dispute was addressed in the German literature by a number of authors. Walther Müller in his monograph "The normal and pathological physiology of the bone" criticized Wolff for his concept of interstitial bone growth. In Müller´s view, HVL applies to the growing bone and Wolff confuses growth with hypertrophy of the mature bone. CONCLUSION: The circumstances of the emergence of HVL are inaccurately and incompletely described in the current literature, as they are mostly taken from secondary sources. HVL, as it is presented today, is not the original formulation, but the result of a long historical evolution.
Keywords: ortopedie; remodelace kosti; Orthopedics; dějiny 19. století; Humans; Growth Plate; Bone Remodeling; vývoj kostí; History, 19th Century; Hueter-Volkmann law; Physis; dějiny 20. století; History, 20th Century; lidé; Bone Development; Bone growth; růstová ploténka; Wollf law; History